Modification of the existing maximum residue levels for propamocarb in radishes (roots and small leaves) - EFSA (European Food Safety Authority); Giulia Bellisai; Giovanni Bernasconi; Luis Carrasco Cabrera; Irene Castellan; Monica delAguila; Lucien Ferreira; Luna Greco; Samira Jarrah; Renata Leuschner; Andrea Mioč; Stefanie Nave; et al. (EFSA Journal)
Abstract In accordance with Article 6 of Regulation (EC) No 396/2005, the Federal Public Service (FPS) Health, Food chain Safety and Environment submitted a request to the competent national authority in Belgium (evaluating Member State, EMS) to modify the existing maximum residue levels (MRLs) for the active substance propamocarb in radishes for the residues occurring in radish roots and in small radish leaves (proposed to be classified under the subgroup of Roman rocket/rucola). The data submitted in support of the request were found to be sufficient to derive MRL proposals for radishes and small radish leaves. Adequate analytical methods for enforcement are available to control the residues of propamocarb on the commodities under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of propamocarb according to the reported agricultural practice is unlikely to present a risk to consumer health. The chronic consumer risk assessment shall be regarded as indicative since affected by uncertainty related to the data gaps identified in the MRL review.